Optimal hot metal desulphurisation slag considering iron loss and sulphur removal capacity part I: fundamentals. (2nd January 2021) - Schrama, Frank N. H.; Beunder, Elisabeth M.; Panda, Sourav K.; Visser, Hessel-Jan; Moosavi-Khoonsari, Elmira; Sietsma, Jilt; Boom, Rob; Yang, Yongxiang
ABSTRACT: In hot metal desulphurisation (HMD) the slag will hold the removed sulphur. However, the iron that is lost when the slag is skimmed off, accounts for the highest costs of the HMD process. These iron losses are lower when the slag has a lower viscosity, which can be achieved by changing the slag composition. A lower slag basicity decreases the viscosity of the slag, but also lowers its sulphur removal capacity, therefore optimisation is necessary. In this study, the optimal HMD slag composition is investigated, considering both the sulphur removal capacity and the iron losses. In part I the theory is discussed and in part II the optimal slag is validated with plant data, laboratory experiments and a thermodynamic analysis.